Immigrant women’s experiences of maternity-care services in Canada: a systematic review using a narrative synthesis - Higginbottom, Gina M.A.; Morgan, Myfany; Alexandre, Mirande; Chiu, Yvonne (BioMed Central, 2015)
Background: Canada’s diverse society and its statutory commitment to multiculturalism means that a synthesis of knowledge related to the healthcare experiences of immigrants is essential to realise the health potential for future Canadians. Although concerns about the maternity experiences of immigrants in Canada are relatively new, recent national guidelines explicitly call for the tailoring of services to user needs. We therefore assessed the experiences of immigrant women accessing maternity-care services in Canada. In particular, we investigated the experiences of immigrant women in Canada in accessing and navigating maternity and related healthcare services from conception to 6 months postpartum in Canada. Our focus was on (a) the accessibility and acceptability of maternity-care services for immigrant women and (b) the effects of the perceptions and experiences of these women on their birth and postnatal outcomes.